Literacy of Sharia in Financial Analysis to Halal Life Style Salatiga Community in 2019 - Bambang Triyono (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2021)
The research objectives include the content and formulation of the research problem. The purpose of this study was to determine the influence of Islamic financial literacy on the halal life style of the people of the city of Salatiga in 2019.The behavior and attitudes of the community need to be realized by inculcating sharia economic values, so that people are able to behave properly according to religious law, not just following trends. So that in this study the researchers included the cultivation of sharia values in order to build a halal life style in the Salatiga community, especially the Muslim community. The importance of inculcating the values of halal life style is that people are able to behave Islamically both in lifestyle and meeting needs. Based on the background of the problem and needs analysis, the formulation of the problem in this study is how to model the cultivation of halal life style values in order to build financial literacy for the Salatiga community. The objectives of this research in general are: to determine the influence of Islamic financial literacy on the halal life style of the people of Salatiga in 2019